# x^2+x=13

## Simple and best practice solution for x^2+x=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for x^2+x=13 equation:

Simplifying x^{2}+ x = 13 Reorder the terms: x + x^{2}= 13 Solving x + x^{2}= 13 Solving for variable 'x'. Reorder the terms: -13 + x + x^{2}= 13 + -13 Combine like terms: 13 + -13 = 0 -13 + x + x^{2}= 0 Begin completing the square. Move the constant term to the right: Add '13' to each side of the equation. -13 + x + 13 + x^{2}= 0 + 13 Reorder the terms: -13 + 13 + x + x^{2}= 0 + 13 Combine like terms: -13 + 13 = 0 0 + x + x^{2}= 0 + 13 x + x^{2}= 0 + 13 Combine like terms: 0 + 13 = 13 x + x^{2}= 13 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x^{2}= 13 + 0.25 Reorder the terms: 0.25 + x + x^{2}= 13 + 0.25 Combine like terms: 13 + 0.25 = 13.25 0.25 + x + x^{2}= 13.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 13.25 Calculate the square root of the right side: 3.640054945 Break this problem into two subproblems by setting (x + 0.5) equal to 3.640054945 and -3.640054945.## Subproblem 1

x + 0.5 = 3.640054945 Simplifying x + 0.5 = 3.640054945 Reorder the terms: 0.5 + x = 3.640054945 Solving 0.5 + x = 3.640054945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 3.640054945 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 3.640054945 + -0.5 x = 3.640054945 + -0.5 Combine like terms: 3.640054945 + -0.5 = 3.140054945 x = 3.140054945 Simplifying x = 3.140054945## Subproblem 2

x + 0.5 = -3.640054945 Simplifying x + 0.5 = -3.640054945 Reorder the terms: 0.5 + x = -3.640054945 Solving 0.5 + x = -3.640054945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -3.640054945 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -3.640054945 + -0.5 x = -3.640054945 + -0.5 Combine like terms: -3.640054945 + -0.5 = -4.140054945 x = -4.140054945 Simplifying x = -4.140054945## Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.140054945, -4.140054945}

### See similar equations:

| -7(2+7x)=-112 | | 4m-3=m | | 4n+2=n+8 | | 6(9x+1)+5x= | | 8x^2=17 | | 5=b+3 | | 9n+4=67 | | 16x-7=8x+17 | | 3x-6=2x+1 | | .33x=9 | | 6x+65=12x+35 | | 46-2x=6-7x | | 5x-6=3x-5 | | 11-8x=122-29x | | 3p+2=23 | | 24e^2-54=0 | | 6x-3=4x+7 | | 3(-1+4x)=33 | | 74-6x=3x+21 | | n*6=7 | | 251.2=2r*3.14 | | (9x+16)-11= | | 11x+2=8x+7 | | (2x+12)+9x= | | 6.28=2r*3.14 | | 6*x+8=56 | | 3x-6y=24 | | 2-3x=x+10 | | 7(7x-9)+9x= | | x+1=2(x-1) | | 5x+6=3x-1 | | X+10-14=16 | | 7x-27=2x+8 | | 6x+7=3x-1 | | 5x^2+9=0 | | 4(-4-3x)=-160 | | 9x+8=7x+3 | | 5x^2-9=0 | | 5(4x+4)+6x= | | -3x^2+12-12=0 | | Y^3-10y^2+21y=0 | | 150.72=2r*3.14 | | 5-3x=11-5x | | -4(1-6x)=-124 | | 4r+7r= | | x^2+6-8=0 | | -7x^2+71x-2=0 | | 13f-4f-7f= | | 3x+2=9+2x | | 5y^2+25y+30=0 | | 16t-7t-8t= | | 2(7x+6)=26 | | 7t-4=1ot+14 | | 3w-6w+2w= | | 5y^2+45y+100=0 | | -a+3y-3a-y= | | 3p+2=23-4p | | 0=16t^2+5t | | -6(1x-1)=-30 | | 64-128x+64=9 | | 263.76=2r*3.14 | | -128x+64=9 | | 20=x+0.12*x | | 3x+2=-22 | | -7(10+6x)=-406 |